2018
DOI: 10.5604/01.3001.0012.1380
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and corrosion resistance of Ni-Co superalloys for gas turbine engines blades

Abstract: Purpose: This paper is devoted to the investigation of gaseous hydrogen and ash gas turbine fuel influence on the mass loss in long-term corrosion and mechanical properties of cast heat-resistant blade materials. It has been established that the level of corrosion resistance of the investigated alloys (Ni59Cr21Co10W4Ti3Al3MoLa (SM-104-VI); Ni57Cr16Co12W6Ti4Al3Mo2Hf (SM-90-VI); Ni57Cr16Co11W6Ti4Al4Mo2Hf (SM-88U-VI)) correlated with the chromium content and is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been found that at low deformation rates (∼1 mm/min) and large hydrogen pressures (∼3 MPa), intergranular destruction and destruction along the boundaries of the carbide matrix occur with cracking of carbides (Figures 8(a) and 8(b)). e change in the nature of the fracture from transgranular to intergranular under the action of hydrogen is a characteristic feature of dispersionhard austenitic steels and alloys due to the concentration at the grain boundaries of carbides, intermetallics, and hydrogen [1,2,4,5,[24][25][26][27]. Figure 7: X-ray patterns of the alloys with different content of carbides (I, II, see Table 1): a, Ni-base solid solution; b, Ni 3 (Al, Mo, Nb); c, (Cr, Ni, Fe) 23 (C, N) 6 .…”
Section: Influence Of Heat Treatment Regimes and Chemicalmentioning
confidence: 99%
“…It has been found that at low deformation rates (∼1 mm/min) and large hydrogen pressures (∼3 MPa), intergranular destruction and destruction along the boundaries of the carbide matrix occur with cracking of carbides (Figures 8(a) and 8(b)). e change in the nature of the fracture from transgranular to intergranular under the action of hydrogen is a characteristic feature of dispersionhard austenitic steels and alloys due to the concentration at the grain boundaries of carbides, intermetallics, and hydrogen [1,2,4,5,[24][25][26][27]. Figure 7: X-ray patterns of the alloys with different content of carbides (I, II, see Table 1): a, Ni-base solid solution; b, Ni 3 (Al, Mo, Nb); c, (Cr, Ni, Fe) 23 (C, N) 6 .…”
Section: Influence Of Heat Treatment Regimes and Chemicalmentioning
confidence: 99%
“…To increase heat resistance and reduce high-temperature corrosion of the blades, chromium is injected from 12 to 20% of the mass in the alloys. The increased chromium content promotes the formation of carbide phases in the alloy, which reduce the ductility of the cast metal [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…to increase the hightemperature strength, the alloys are alloyed with a high chromium content. however, a high chromium content can cause the appearance of topologically close-packed phases of the μ, σ type in the casting structure during the development process, which will lead to phase-structural instability and embrittlement of parts [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%